Meiotic chromosomes and sex determination mechanism in Thailand and Hawaii isolates of Angiostrongylus cantonensis (Nematoda: Angiostrongylidae) - Eamsobhana, Praphathip; Yoolek, A.; Yong, Hoi Sen (Malaysian Society of Parasitology and Tropical Medicine, 2009)
Angiostrongylus cantonensis, the nematode lungworm of rats, has a XX/X0 sex-determination mechanism. The chromosome constitution consists of 10 autosomes, with 2n = 12, XX in the female and 2n = 11, X0 in the male. Meiosis-I shows five bivalents and one univalent for the male worm, and six bivalents for the female worm. The chromosome constitution of the Thailand and Hawaii isolates of A. cantonensis is similar to those reported for the taxa from Japan, Egypt and mainland China.